Sentence comprehension test for Russian: A tool to assess syntactic competence - Chernova, Daria; Novozhilov, Artem; Slioussar, Natalia (Frontiers in Psychology, 2023)
Although all healthy adults have advanced syntactic processing abilities in their native language, psycholinguistic studies report extensive variation among them. However, very few tests were developed to assess this variation, presumably, because when adult native speakers focus on syntactic processing, not being distracted by other tasks, they usually reach ceiling performance. We developed a Sentence Comprehension Test for the Russian language aimed to fill this gap. The test captures variation among participants and does not show ceiling effects. The Sentence Comprehension Test includes 60 unambiguous grammatically complex sentences and 40 control sentences that are of the same length, but are syntactically simpler. Every sentence is accompanied by a comprehension question targeting potential syntactic processing problems and interpretation errors associated with them. Grammatically complex sentences were selected on the basis of the previous literature and then tested in a pilot study. As a result, six constructions that trigger the largest number of errors were identified. For these constructions, we also analyzed which ones are associated with the longest word-by-word reading times, question answering times and the highest error rates. These differences point to different sources of syntactic processing difficulties and can be relied upon in subsequent studies. We conducted two experiments to validate the final version of the test. Getting similar results in two independent experiments, as well as in two presentation modes (reading and listening modes are compared in Experiment 2) confirms its reliability. In Experiment 1, we also showed that the results of the test correlate with the scores in the verbal working memory span test.